2002
DOI: 10.1037/0022-006x.70.3.678
|View full text |Cite
|
Sign up to set email alerts
|

Psychological factors in chronic pain: Evolution and revolution.

Abstract: Research has demonstrated the importance of psychological factors in coping, quality of life, and disability in chronic pain. Furthermore, the contributions of psychology in the effectiveness of treatment of chronic pain patients have received empirical support. The authors describe a biopsychosocial model of chronic pain and provide an update on research implicating the importance of people's appraisals of their symptoms, their ability to self-manage pain and related problems, and their fears about pain and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
569
2
40

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 764 publications
(637 citation statements)
references
References 102 publications
26
569
2
40
Order By: Relevance
“…Some may say that the appropriate choice of model underlying CBT today is the biopsychosocial (BPS) model. 21,78 The BPS model can help integrate at a level of multidisciplinary cooperation and certainly it has great advantages over biomedical reductionism. We certainly agree that work in separate fields in the study of pain should integrate.…”
Section: Psychological Flexibility and Chronic Pain 25mentioning
confidence: 99%
“…Some may say that the appropriate choice of model underlying CBT today is the biopsychosocial (BPS) model. 21,78 The BPS model can help integrate at a level of multidisciplinary cooperation and certainly it has great advantages over biomedical reductionism. We certainly agree that work in separate fields in the study of pain should integrate.…”
Section: Psychological Flexibility and Chronic Pain 25mentioning
confidence: 99%
“…Turk and colleagues, for example, have revealed that patients with diseases and syndromes as varied as back pain, headache, and metastatic cancer may display comparable adaptation patterns, whereas patients with the same diagnosis may actually show great variability in their degree of disability (e.g., Turk, Okifuji, Sinclair, & Starz, 1998). As Turk and Gatchel (1999) have indicated, the traditional approach of "lumping" patients with the same medical diagnosis or set of symptoms together (e.g., fibromyalgia, LBP, TMD), and then to treat them all the same way, is not appropriate. That is because many of these common diagnoses are relatively gross categories, and there may be unique individual BPS differences of patients who fall under these generic diagnoses.…”
Section: Patient Heterogeneity and Response To Treatmentmentioning
confidence: 99%
“…The biopsychosocial model of pain suggests that medical illness, individual life history, environmental factors, and social relationships are all important for understanding and treating chronic pain (Turk & Okifuji, 2011). …”
Section: Introductionmentioning
confidence: 99%